Pengaruh Kualitas Pelayanan, Citra Perusahaan Dan Persepsi Harga Terhadap Kepuasan Pelanggan Pada PT. Major Sukses Berkah - Renaldi Ridho Nugroho; Ni Ketut Seminari (Public Service and Governance Journal, 2023)
Customer satisfaction is one of the factors or measures of success for any development in a business. The purpose of the study was to analyze the effect of service quality, corporate image and price perception on customer satisfaction at PT. Major Success Blessing. The population in this study are registered clients from 2021, which are 56 clients. The sampling method used in this research is saturated sample. Methods of data collection using a questionnaire. The data analysis technique used multiple linear regression analysis. The results of research on service quality, corporate image and price perception simultaneously have a significant effect on customer satisfaction at PT. Major Success Blessing. Service quality has a positive and significant effect on customer satisfaction of PT. Major Success Blessing. Company image has a positive and significant effect on customer satisfaction of PT. Major Success Blessing. Price perception has a positive and significant effect on customer satisfaction of PT. Major Success Blessing.